Augmented Reality Model for Pre-School Learning - Huda Wahida, Rosli (2013)
Science subject is very important to create scientific knowledge among students. In Malaysia, the implementation of the Science Curriculum is normally done via conventional approach. However, this approach is not able to attract students’ interests in exploring more knowledge. In addition, the students only acquire the basic knowledge without being able to visualize the subject matters. Thus, this study is aimed to apply Augmented Reality (AR) technology in teaching and learning of the Basic Science subject to overcome the issues. AR is the augmentation of the real world through the addition of three-dimensional (3D) virtual objects. AR has been proven as an effective method in delivering lessons to the students compared to conventional method. This study applied AR in preschool Basic Science subject that focused on the internal organ of human body known as the Muscular System. This study adapted AR with Experiential Learning Model (ELM) theory to construct the requirement model of the Augmented Reality for Learning in Muscular System (ARMS). The proposed model consisted of three (3) main components; i) Requirement to Implement AR in a Classroom (R-IARC), ii) High-Level Prototyping (HLP), and iii) Experiential Learning Model (ELM). The methodology in this study involved five (5) main phases; i) theoretical study, ii) preliminary study, iii) requirement model construction, iv) ARMS development, v) model evaluation by users and experts respectively. The requirement of the proposed model was collected using multiple facts finding techniques, namely interview, observation, and document reviews. The proposed model was validated using prototyping approach. The evaluation of the prototype was done by expert reviews and end-user acceptance study. The results of the evaluation showed that the ARMS was highly effective to be implemented in the teaching and learning of Basic Science subject. This is because it assists in explaining difficult topics. In addition, it has also been proven that the integration of the AR technology in teaching and learning is able to create an enjoyable environment because it is supported by the visualization of 3D virtual objects. As a result, the students were able to understand and recognize the functions, health, and diseases of the muscular system through ARMS. The study also found that the implementation of ARMS was able to increase the students’ cognitive development and enhance the students’ learning ability.